Revisiting tourism studies curriculum to highlight accessible and inclusive tourism - Liasidou, Sotiroula; Umbelino, Jorge; Amorim, Éricka (My University, 2019)
A notable development in the past few years is that the concept of accessible and inclusive tourism (AIT) has gained momentum. This paper has two aims: first, to identify the extent to which tourism studies curricula can cultivate ethical behaviour in light of international legal mandates and conventions promoting the rights of people with disabilities (PwDs); and second, to point up AIT as a broader concept that matters to other population groups, namely seniors, pregnant women and families with baby carriages, people who follow special diets or have different morphologies to be integrated into the much larger category of people with special needs (PwSNs). This study was conducted with 254 self-administered questionnaires to tourism and hospitality students and recent alumni. The results of the study suggest that disability in tourism studies is a rather neglected topic of discussion.
Keywords: Accessible and inclusive tourism; Special needs; Tourism curriculum; Tourism education